PENINGKATAN KETERAMPILAN BERBICARA MELALUI LITERASI DIGITAL DENGAN METODE CASE BASED LEARNING (CBL) DALAM PEMBELAJARAN TEKS BERITA PADA SISWA KELAS VIII C SMP SAPTA ANDIKA - Dewi Shintiyah; Ida Ayu Made Wedasuwari; I Nyoman Adi Susrawan (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2023)
This study is a class action study (PTK) aimed at 1) Knowing the improvement of speaking skills through digital literacy using case based learning (CBL) methods in the VIII C class of Sapta Andika Junior High School; 2) Knowing the steps of case based learning (CBL) methods in improving speaking skills through digital literacy in news text learning in the VIII C class of Sapta Andika Junior High School. Data collection is done by interview, observation, and test methods. The data obtained are analyzed using quantitative analysis techniques. The results of the study showed that there was an increase in speaking skills through digital literacy using case-based learning (CBL) methods in news text learning in Sapta Andika Junior High School VIII C grade students. This can be seen from the student’s average learning score, which is in the pretest of getting an average test score of 67,67. Then, in cycle I get an average test result of average test score of 75,93. Also, in cycle II, the average test score was 79,65.